Improvement of Physical Activity in Volleyball Using Outdoor Laboratory in University Education Park - David Richardo Sugiyanto; Hartati Hartati; Silvi Aryanti (Journal of Innovation in Educational and Cultural Research, 2023)
This study aims to determine the physical activity of volleyball players at Indralaya Utara 2 Junior High School.This research is quantitative research with a descriptive research design.The subjects of this study were volleyball players at Indralaya Utara 2 Junior High School with a total of 30 players consisting of 22 boys and 8 girls.Data collection used a test.The research location was carried out in an outdoor laboratory in the University Education Park.The data analysis technique uses descriptive analysis, which is expressed in the form of a percentage.The results of the study found that the physical activity of volleyball players which included endurance, speed, arm muscle strength, abdominal muscle strength, and leg muscle explosive power was in the moderate category and there were 3 players in the very good category, 6 players in the good category, 11 players in the fair category, 9 players in the poor category, 1 player in the very poor category.It can be concluded that the physical activity of volleyball players at Indralaya Utara 2 Junior High School is in the sufficient category. some of the findings have implications for the results of the research, namely the emergence of awareness for both players and students to increase and maintain physical activity wherever and whenever to improve the physical condition of players who are still in the sufficient category and still not enough so they can get better.